Preparation and characterization of polymer electrlytes based on epoxidized natural rubber and polymethyl methacrylate - 300204 Cheong, Wai Wan (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2005